If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -5x + -15 = 8x + 13 + -6x Reorder the terms: 14 + -15 + -5x = 8x + 13 + -6x Combine like terms: 14 + -15 = -1 -1 + -5x = 8x + 13 + -6x Reorder the terms: -1 + -5x = 13 + 8x + -6x Combine like terms: 8x + -6x = 2x -1 + -5x = 13 + 2x Solving -1 + -5x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + -5x + -2x = 13 + 2x + -2x Combine like terms: -5x + -2x = -7x -1 + -7x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + -7x = 13 + 0 -1 + -7x = 13 Add '1' to each side of the equation. -1 + 1 + -7x = 13 + 1 Combine like terms: -1 + 1 = 0 0 + -7x = 13 + 1 -7x = 13 + 1 Combine like terms: 13 + 1 = 14 -7x = 14 Divide each side by '-7'. x = -2 Simplifying x = -2
| 2x+72=5x | | 7xy+9xy=96whatisy | | 80=100-9.1(x-1.9) | | 4g+7=-5g-1+g | | 0.8=100-9.1(x-1.9) | | =(-2p^3-5p+7)+(-4p^2+8p+2) | | 5+3k=-16 | | 10000=x-3000 | | 10000a=2x-3000 | | -7(6+7p)+7(8p+3)=-35 | | -3x-8=-8+3x | | -6(3-6k)+2(8-5k)=-54 | | 3x(4x+9)= | | -120=6(-6-7x) | | -3x^2-22x-7=0 | | -6x^2+5x+21=0 | | -88=-4(-6+7v) | | -4x^2-2x+56=0 | | -3(-4a-5)+6a=105 | | 44=6x-12y | | 44=6x-12 | | 6x-12y=44 | | -2x^2-22x-48=0 | | -3x^2-20x-32=0 | | 2y=6x+10 | | -6x^2-12x+48=0 | | -192=-8(1-3x)+8 | | 3x-1=x+2 | | 4(5x+4)-6= | | 2(3x+2)-3= | | 3(8y-8)-(2y+2)= | | 6(9y-5)-(6y+8)= |